Mary Macarthur's election manifesto, 1918 (page 3) (1918)
1918 "Mary Macarthur's election manifesto, 1918 (page 3)" [T0250b.jpg], 1918 Mary Macarthur, secretary of the National Federation of Women Workers, stood as Labour Party candidate in Stourbridge, Worcestershire at the General Election on 14 December, 1918.